Mucosal melanoma of the upper airways tract mucosal melanoma: A systematic review with meta‐analyses of treatment. Issue 4 (29th November 2016) - Jarrom, David; Paleri, Vinidh; Kerawala, Cyrus; Roques, Thomas; Bhide, Shreerang; Newman, Laurence; Winter, Stuart C.
ABSTRACT: Background: Mucosal melanoma of the upper aerodigestive tract (MM‐UADT) occurs in a complex anatomic region. It represents a small number of tumors of the head and neck and a small number of melanoma cases. Methods: Search strategies initially identified 600, 11 of which were included in this study. Results: All studies involved surgery and radiotherapy. None were randomized, and all were assessed as having a high risk of selection and performance bias. No studies reported quality of life, treatment‐related mortality, or morbidity. The results indicate that the addition of radiotherapy to surgery reduces the rate of locoregional recurrence (hazard ratio [HR], 0.60; 95% confidence interval [CI], 0.42–0.87). There was no statistically significant difference in overall survival (HR, 1.16; 95% CI, 0.98–1.37). Conclusion: Surgical resection with postoperative radiotherapy remains the optimal treatment strategy for locoregional control. More robust studies and the use of molecular targeted therapies need to be undertaken to improve overall survival. © 2016 Wiley Periodicals, Inc. Head Neck 39: 819–825, 2017